2019
DOI: 10.2134/jeq2018.10.0371
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Artificial Nano‐Hydroxyapatite in the Presence of Natural Colloids: Influence of Steric Forces and Chargeability

Abstract: The stability of nano-hydroxyapatite (nHAP) affects its fate in the environment. Few studies have compared the influence of colloids with different properties on the stability of nHAP. Fulvic acid, montmorillonite, and goethite were chosen as representative colloids. An ultraviolet-visible spectrophotometer and NanoBrook 90Plus phase analysis light scattering (PALS) were used to determine absorbance, zeta potential, and hydrodynamic diameter. Results showed that addition of fulvic acids could make nHAP more st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…As reported by Hansen et al [46], it was found that as the pH of the initial mixture increased, the aggregation of the synthesized hydroxyapatite crystals increased, which resulted in a decrease in both the specific surface area and adsorption capacity [47]. This phenomenon could be as a result of the surface energy of hydroxyapatite crystals [46,48]. The higher alkaline condition led to a higher surface energy of hydroxyapatite crystals, and it led to the aggregation of hydroxyapatite crystals [46,49].…”
Section: Morphology and Particle Sizementioning
confidence: 73%
“…As reported by Hansen et al [46], it was found that as the pH of the initial mixture increased, the aggregation of the synthesized hydroxyapatite crystals increased, which resulted in a decrease in both the specific surface area and adsorption capacity [47]. This phenomenon could be as a result of the surface energy of hydroxyapatite crystals [46,48]. The higher alkaline condition led to a higher surface energy of hydroxyapatite crystals, and it led to the aggregation of hydroxyapatite crystals [46,49].…”
Section: Morphology and Particle Sizementioning
confidence: 73%
“…Sedimentation of heteroaggregates of goethite and Fe 3 O 4 NP with PS NPs or montmorillonite suspensions in the cell was monitored by ultraviolet-visible spectroscopy using an 8453 UV-Vis spectrometer (Agilent Technologies, Santa Clara, CA, USA). Measurements were obtained from the time-resolved optical density (OD = C e [absorbance at different time intervals]/C 0 [initial absorbance]) of heteroaggregates of goethite and Fe 3 O 4 NP suspensions at 441 and 381 nm over 120 min time periods, respectively (Wu et al 2022a;Wu and Bi 2019).…”
Section: Heteroaggregation and Sedimentation Of Goethite And Fe 3 O 4...mentioning
confidence: 99%